2018
DOI: 10.1016/j.chiabu.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the impact of child custody loss on drug use and crime among a sample of African American mothers

Abstract: This study highlights the need to integrate drug treatment and other types of assistance into family case plans to improve reunification rates and outcomes among mothers, children, and families. Additionally, the finding that informal loss predicts increased drug use suggests that community-based efforts within the mother's social network could be implemented to intervene before child welfare system involvement becomes necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Harms to the parent–child dyad caused by involvement in the CWS, such as an increase in parental substance use, trauma, and worse health outcomes for children, are often not weighed against potential harm of parental substance use. 65 The CWS often defaults to separation rather than focusing financial, medical, and societal resources into supporting the family.…”
Section: Substance Use Impact On Pregnancy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Harms to the parent–child dyad caused by involvement in the CWS, such as an increase in parental substance use, trauma, and worse health outcomes for children, are often not weighed against potential harm of parental substance use. 65 The CWS often defaults to separation rather than focusing financial, medical, and societal resources into supporting the family.…”
Section: Substance Use Impact On Pregnancy Outcomesmentioning
confidence: 99%
“…These injustices adversely impact the parent, child, and family thus continuing a cycle of stigma, discrimination, and disparities that passes from one generation to the next. 47 , 65 , 71 …”
Section: Substance Use Impact On Pregnancy Outcomesmentioning
confidence: 99%
“…Thus, navigating a return to society while also providing for their children and potentially regaining custody can severely hinder Black women's successful reintegration. Playing an active role in their children's lives is essential because research finds that Black women who experience child custody loss are more likely to engage in crime (Harp & Oser, 2018).…”
Section: Incarcerated Black Women and Mothersmentioning
confidence: 99%
“…Recent studies of African American mothers in one U.S. state found that not only did substance use and criminal involvement increase the likelihood a mother would lose custody of her children (Harp and Oser 2016) but that maternal substance use and criminal involvement actually increased in the months after custody loss (Harp and Oser 2018). Thus, these punitive CWS policies have a negative effect on mothers struggling to cope with the loss of their children, and rather than decrease maternal drug use, may contribute to an increase in these behaviors, thus reducing a mother's chances of being rehabilitated and reunited with her children.…”
Section: Over-involvement In the Cws And Its Effectsmentioning
confidence: 99%